2013
DOI: 10.1177/0022034513513034
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed TGF-β in Subchondral Bone Leads to Mandibular Condyle Degradation

Abstract: Emerging evidence has implied that subchondral bone plays an important role during osteoarthritis (OA) pathology. This study was undertaken to investigate whether abnormalities of the condylar subchondral bone lead to temporomandibular joint (TMJ) OA. We used an osteoblast-specific mutant TGF-β1 transgenic mouse, the CED mouse, in which high levels of active TGF-β1 occur in bone marrow, leading to abnormal bone remodeling. Subchondral bone changes in the mandibular condyles were investigated by micro-CT, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 25 publications
5
51
0
2
Order By: Relevance
“…In contrast, systemic administration of either strontium or NBD peptide induces no significant changes in non-UAC control condylar cartilage, and slightly increases the values of BV/TV and opg/rankl mRNA ratio in the subchondral bone. These findings are supported by the recent finding that abnormal remodeling of subchondral bone caused by activation of TGF-β signaling leads to OA-like pathological changes in cartilage of both knee and TMJs 32,33 , and inhibition of the TGF-β signaling could largely attenuate cartilage degeneration 32 . What deserves to be mentioned is that there were indeed profound cell losses in the fibrous layer, as well as in the proliferative layer of the articular cartilage in UAC groups.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast, systemic administration of either strontium or NBD peptide induces no significant changes in non-UAC control condylar cartilage, and slightly increases the values of BV/TV and opg/rankl mRNA ratio in the subchondral bone. These findings are supported by the recent finding that abnormal remodeling of subchondral bone caused by activation of TGF-β signaling leads to OA-like pathological changes in cartilage of both knee and TMJs 32,33 , and inhibition of the TGF-β signaling could largely attenuate cartilage degeneration 32 . What deserves to be mentioned is that there were indeed profound cell losses in the fibrous layer, as well as in the proliferative layer of the articular cartilage in UAC groups.…”
Section: Discussionsupporting
confidence: 68%
“…We also did not observe the fibrillation in Tgfbr2 -deficient mice at 12 weeks after the partial discectomy. In line of the observation from this study, another independent research group reports that the increase in the expression of Tgf-β1 in the subchondral bone of TMJ in mice causes early onset condylar cartilage degeneration [20]. Based on these results, we conclude that inhibiting activity of TGF-β1 signaling in mature condylar cartilages can, in fact, protect the cartilages from being degraded.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in line with our data showing increased osteoclast numbers in regions with subchondral osteosclerosis in advanced knee OA. Further evidence for uncoupled bone remodeling as underlying mechanism for OA progression has been recently demonstrated in experimental OA models . In these models, altered mechanical loading induced subchondral bone resorption followed by enhanced recruitment of osteoprogenitors and formation of osteoid islets in marrow spaces.…”
Section: Discussionmentioning
confidence: 93%
“…Molecular changes to human subchondral osteoblasts, including elevated expression of alkaline phosphatase and transforming growth factor‐beta1 (TGF‐β1) and blunted matrix mineralization in vitro, have been implied to be involved the onset and/or progression of OA . Recent investigations in experimental OA and osteoblast‐specific mutant TGF‐β1 transgenic mice have shown that spatiotemporal uncoupling of osteoclastic bone resorption and TGF‐β1‐induced recruitment of mesenchymal stem cells in the subchondral marrow compartment leads to aberrant bone formation and development of OA . Compositional changes of the subchondral marrow compartment in human OA have been frequently observed using magnetic resonance imaging (MRI) and these bone marrow lesions are a prognostic factor for OA progression and correlate spatially with sites of cartilage degeneration …”
mentioning
confidence: 99%